CREATING VALUE IN THE COMPANY: THE CONTINUING STRATEGY - Orna Barillas, Jesús Martín (2015)
In today’s economic environment, companies have to compete not only against other companies, but also by creating new markets that meet the needs of consumers. This is within its external environment. In the domestic environment they have to change their internal operations for achieving efficiency and effectiveness, translated into the creation of value for consumers through products or services that meet their needs, it will create a protective barrier against competitors , workers will be rewarded for their efforts on behalf of the company, the company itself - by improving their processes based on the achievement of efficiency and cost reduction- will get a return that allows it to continue operations; and to owners, based on the profitability of the company , will gain economic benefits. Therefore it indicates that the company, to have sustainable profitability over time, must create value internally in their processes, analyzing the value chain, in line with a proper strategic planning.